Prediction and Identification of Power Performance Using Polygenic Models of Three Single-Nucleotide Polymorphisms in Chinese Elite Athletes - Yang, Ruoyu; Jin, Feng; Wang, Liyan; Shen, Xunzhang; Guo, Qi; Song, Haihan; Hu, Jingyun; Zhao, Qiang; Wan, Jian; Cai, Ming (Frontiers in Genetics, 2021)
Objective: The manuscript aims to explore the relationship between power performance and SNPs of Chinese elite athletes and to create polygenic models. Methods: 103 Chinese elite athletes were divided into power group (n=60) and endurance group (n=43) by their sports event. Best standing long jump (SLJ) and standing vertical jump (SVJ) were collected. 20 SNPs were genotyped by SNaPshot. Genotype distribution and allele frequency were compared between groups. Additional genotype data of 125 Chinese elite athletes were used to verify the screened SNPs. Predictive and identifying models were established by multivariate logistic regression analysis. Results: ACTN3 (rs1815739), ADRB3 (rs4994), CNTFR (rs2070802) and PPARGC1A (rs8192678) were significantly different in genotype distribution or allele frequency between groups (P<0.05). The predictive model consisted of ACTN3(rs1815739), ADRB3(rs4994) and PPARGC1A(rs8192678), the area under curve (AUC) of which was 0.736. The identifying model consisted of BMI, SVJ, ACTN3, ADRB3 and PPARGC1A, the AUC of which was 0.854. Based on the two models, nomograms were created to visualize the results. Conclusion: Two models can be used for talent identification in Chinese athletes, among which the predictive model can be used in adolescent athletes to predict development potential of power performance and the identifying one can be used in elite athletes to evaluate power athletic status. These can be applied quickly and visually by using nomograms. When the score is more than 130 or 148 of cutoff, it suggests that the athlete has a good development potential or a high level for power performance.